Hydrogen bond formation may enhance RDC-based discrimination of enantiomers - Sager, Emine (Magnetic resonance in chemistry : MRC, 2024)
© 2024 The Authors. Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd.